2020
DOI: 10.1038/s41396-020-0700-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-colony channels in E. coli function as a nutrient uptake system

Abstract: The ability of microorganisms to grow as aggregated assemblages has been known for many years, however their structure has remained largely unexplored across multiple spatial scales. The development of the Mesolens, an optical system which uniquely allows simultaneous imaging of individual bacteria over a 36 mm2 field of view, has enabled the study of mature Escherichia coli macro-colony biofilm architecture like never before. The Mesolens enabled the discovery of intra-colony channels on the order of 10 μm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 59 publications
9
62
0
Order By: Relevance
“…For example, Wilking et al [ 29 ] suggested that the abovementioned network of channels facilitates liquid transport throughout the macrocolonies with evaporative flux acting as the driving force. A complementary force that allows the macrocolonies to uptake nutrients from the growth substrate was also suggested by Gingichashvili et al [ 12 ], while a similar channel-driven nutrient uptake and distribution effect was previously reported in E. coli biofilms [ 30 ]. Analysis of macrocolonies that were co-cultured and grown in a mixture with fluorescent microspheres reveals two additional forces present in B. subtilis macrocolonies.…”
Section: Discussionsupporting
confidence: 61%
“…For example, Wilking et al [ 29 ] suggested that the abovementioned network of channels facilitates liquid transport throughout the macrocolonies with evaporative flux acting as the driving force. A complementary force that allows the macrocolonies to uptake nutrients from the growth substrate was also suggested by Gingichashvili et al [ 12 ], while a similar channel-driven nutrient uptake and distribution effect was previously reported in E. coli biofilms [ 30 ]. Analysis of macrocolonies that were co-cultured and grown in a mixture with fluorescent microspheres reveals two additional forces present in B. subtilis macrocolonies.…”
Section: Discussionsupporting
confidence: 61%
“…Several of these approaches were already used to examine phage-biofilm interactions, namely epifluorescence microscopy, CLSM (95), scanning electron microscopy (SEM) (96), field emission SEM (90), and atomic force microscopy (97). An optical system that allows simultaneous imaging of individual bacterial cells over a 36-mm 2 field of view was recently developed (98). With this system, E. coli biofilms were observed in a detail never seen before, and new intracolony channels with an approximately 10-µm diameter were discovered (98).…”
Section: Microscopy Methodsmentioning
confidence: 99%
“…An optical system that allows simultaneous imaging of individual bacterial cells over a 36-mm 2 field of view was recently developed (98). With this system, E. coli biofilms were observed in a detail never seen before, and new intracolony channels with an approximately 10-µm diameter were discovered (98).…”
Section: Microscopy Methodsmentioning
confidence: 99%
“…As expected araF STEC (pACYC araF STEC :: gfp +, pJM066) was induced in xylose as it is a low-affinity xylose transporter, but at a reduced level compared to arabinose (Supplementary Table 2). Utility of araBA STEC (pACYC araBAD STEC ::gfp+ , pJM058) was also demonstrated during biofilm formation of non-pathogenic E. coli [32]. Therefore, the promoter constructs could effectively be used as specific biosensors for the presence of L-arabinose.…”
Section: Resultsmentioning
confidence: 99%